Difficulties in screening for peripheral neuropathies in children with diabetes. Issue 6 (30th January 2015) - Hirschfeld, G.; von Glischinski, M.; Knop, C.; Wiesel, T.; Reinehr, T.; Aksu, F.; Blankenburg, M.; Hirsch, J.; Zernikow, B.
Abstract Aims To assess the diagnostic utility of a novel abbreviated monofilament test in comparison with the tuning fork test to detect diabetic peripheral neuropathy in children. Methods A total of 88 children with Type 1 diabetes mellitus were screened for diabetic peripheral neuropathy using the monofilament test and the tuning fork. Nerve conduction studies were performed according to the 'gold standard' for neuropathy. We assessed the diagnostic utility and inter‐rater agreement of the two screening methods. Results A total of 43 (49%) children (aged 6–18 years) had at least one abnormal nerve conduction study result. Diagnostic utility and inter‐rater agreement were very low for both screening methods. The monofilament test yielded a sensitivity of 18% and a specificity of 80%. The tuning fork yielded a sensitivity of 0% and a specificity of 98%. Conclusion The present study found that an abbreviated monofilament test has low diagnostic utility for the detection of early diabetic peripheral neuropathy because of its low reliability. The problem of reliability needs to be more thoroughly addressed in order to improve the screening procedures in diabetes management in childhood and adolescence.